Trained nurses’ knowledge and practice of oral care on three wards in acute care hospital in Abu Dhabi, UAE - Belal, Hijji (Online Brazilian Journal of Nursing, 2004)
Background.Mouth care is an essential nursing procedure that nurses are expected to have good knowledge of. Poor knowledge may compromise the quality of patient care and result in unsafe practice. Documentation of nurses’ current knowledge and practice is crucial if improvement efforts are to proceed.Aims. To investigate nurses’ reported knowledge and practice of oral care, to identify the relationship between nurses’ knowledge and practice and their demographics, and to identify nurses' perceived barriers to good practice.Methods.Cross-sectional descriptivesurvey. 58 nurses on three wards represented the target population. The questionnaire generated information about personal data, education and level of knowledge and practice of mouth care.Results.46 nurses (79%) completed the questionnaire. Questionnaire analysis revealed knowledge deficits about several important aspects of oral care and inadequate practice.However, no statistically significant differences were detected among groups.Lack of materials, lack of time, and uncooperative patients were perceived barriers to good practice.Conclusion.It is now time for action. Paste and brush should be regularly provided. Hydrogen Peroxide 3% to be withdrawn. Nurses’s knowledge to be improved. Individual results to be disseminated to each ward.